Microsoft Office Professional 2013 for touch devices plain & simple - Murray, Katherine, 1961- (Plain & simple., 2013)
Learn the simplest ways to get things done with Microsoft Office 2013 for Tablets Get the full-color, visual guide that makes learning Microsoft Office 2013 on your touch-enabled devices plain and simple! Follow the book's easy steps and screenshots and clear, concise language to learn the simplest ways to get things done with Microsoft Word, Excel, Outlook, PowerPoint, Access, Publisher, and OneNote--all in touch mode. Here's WHAT you'll learn: Tap the power of Office on your touch device Stay in the loop with Ims, social media, and email Create, share, and collaborate on documents Put together professional-looking publications Analyze your worksheet data on the fly Set up an online meeting with your team Here's HOW you'll learn it: Jump in wherever you need answers Follow easy STEPS and SCREENSHOTS to see exactly what to do Get handy TIPS for new techniques and shortcuts Use TRY THIS! Exercises to apply what you learn right away.